2005
DOI: 10.1097/01.psy.0000181279.06164.6e
|View full text |Cite
|
Sign up to set email alerts
|

Sympathoimmune Anomalies Underlying the Response to Stressful Challenge in Human Immunodeficiency Virus Spectrum Disease

Abstract: Early in HIV spectrum disease, functional abnormalities in the stress-induced migratory ability of specific immunocellular subsets are present that may reflect an underlying pathophysiological alteration in sympathoimmune communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Prior to school entry, HIV+ children had fewer CD4+ cells, more CD8+ cells, and less NK cell lytic activity than their HEU counterparts. These differences are consistent with current understanding of HIV pathophysiology (41, 42) and with a previous study comparing immune reactivity between HIV+ and HIV− adults (19). The present finding offers replication of previously observed immune differences between HIV+ and HIV− individuals and extends findings to the pediatric population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Prior to school entry, HIV+ children had fewer CD4+ cells, more CD8+ cells, and less NK cell lytic activity than their HEU counterparts. These differences are consistent with current understanding of HIV pathophysiology (41, 42) and with a previous study comparing immune reactivity between HIV+ and HIV− adults (19). The present finding offers replication of previously observed immune differences between HIV+ and HIV− individuals and extends findings to the pediatric population.…”
Section: Discussionsupporting
confidence: 91%
“…Autonomic nervous system (ANS) reactivity has been shown to be a potential mediator between psychological factors such as social inhibition and the progression of HIV-illness (17) and a moderator of associations between adversity and clinical course among children with a chronic disease (18). ANS reactivity has been shown to differentially affect immunocellular responses among HIV+ and HIV− adults following an acute laboratory stressor (19). …”
Section: Introductionmentioning
confidence: 99%
“…Unlike progesterone, AlloP is a potent, positive allosteric modulator of GABA A receptors (Majewska et al, 1986; Paul & Purdy, 1992), a potential negative allosteric modulator of NMDA receptors (Johansson & Le Grevès, 2005; Maurice et al, 2006), is produced in response to immune challenge (Billiards et al, 2002; Ghezzi et al, 2000), and can reduce excitotoxicity partly through rapid increases of tonic inhibition in models of CNS insult (Baulieu & Schumacher, 2000; Brunton et al, 2014; Mellon et al, 2008; Sayeed & Stein, 2009). Allopregnanolone is produced rapidly in response to stress challenges to restore sympathetic and parasympathetic tone (Barbaccia et al, 1996; Patchev et al, 1994, 1996), functions which are observed to be dysregulated among some HIV + individuals (Chittiprol et al, 2007, 2008; Hurwitz et al, 2005). In ovariectomized female mice, supra-physiological progesterone attenuated the anxiety-like effects of HIV-1 Tat exposure (Paris et al, 2014a); however, the mechanisms underlying behavioral protection, the involvement of pregnane steroids on neuroinflammation, and the importance of neurosteroid formation were not assessed.…”
Section: Introductionmentioning
confidence: 99%
“…There was also evidence that higher urinary cortisol was associated with fewer subsets of naive CD4+ T cells in the HAART era ( 26 ), and more diurnal variation in salivary cortisol (thought to be a healthy pattern) was associated with less CD4+ T-cell and CD8+ T-cell activation in PWH who were ART naive ( 29 ). The relevance of the autonomic nervous system in HIV pathogenesis is further supported by a reactivity study examining a speech stressor task where PWH (compared with people without HIV) displayed greater stress-induced increases in activated CD8+ CD38+ T cells, smaller increases in natural killer cell number and cytotoxicity, and suppression of the T-cell lymphoproliferative response to phytohemagglutinin mitogen, which are each indicative of immune dysregulation ( 30 ). The associations of catecholamines such as epinephrine with these stress-induced immunologic changes varied by HIV status, suggesting functional alterations in the communication of the sympathetic nervous system with the immune system among PWH.…”
Section: That Was Then: Pni Studies Conducted Through the Haart Eramentioning
confidence: 99%